Three Dimensional Cultures: A Tool To Study Normal Acinar Architecture vs. Malignant Transformation Of Breast Cells - Pal, Anupama (MyJove Corporation, 2014)
Invasive breast carcinomas are a group of malignant epithelial tumors characterized by the invasion of adjacent tissues and propensity to metastasize. The interplay of signals between cancer cells and their microenvironment exerts a powerful influence on breast cancer growth and biological behavior(1). However, most of these signals from the extracellular matrix are lost or their relevance is understudied when cells are grown in two dimensional culture (2D) as a monolayer. In recent years, three dimensional (3D) culture on a reconstituted basement membrane has emerged as a method of choice to recapitulate the tissue architecture of benign and malignant breast cells. Cells grown in 3D retain the important cues from the extracellular matrix and provide a physiologically relevant ex vivo system(2,3). Of note, there is growing evidence suggesting that cells behave differently when grown in 3D as compared to 2D(4). 3D culture can be effectively used as a means to differentiate the malignant phenotype from the benign breast phenotype and for underpinning the cellular and molecular signaling involved(3). One of the distinguishing characteristics of benign epithelial cells is that they are polarized so that the apical cytoplasm is towards the lumen and the basal cytoplasm rests on the basement membrane. This apico-basal polarity is lost in invasive breast carcinomas, which are characterized by cellular disorganization and formation of anastomosing and branching tubules that haphazardly infiltrates the surrounding stroma. These histopathological differences between benign gland and invasive carcinoma can be reproduced in 3D(6,7). Using the appropriate read-outs like the quantitation of single round acinar structures, or differential expression of validated molecular markers for cell proliferation, polarity and apoptosis in combination with other molecular and cell biology techniques, 3D culture can provide an important tool to better understand the cellular changes during malignant transformation and for delineating the responsible signaling.